(untitled) (Al-Academy, 2020)
The field of graphic design has witnessed a unique, unique form transformed in its construction and installation and superior to systems through its creation of foundational data for design ideas with functional aesthetics and utilitarianism and effective and moving formulation in light of modern trends and what globalization has brought about in terms of openness to the outside world and the processes of communication and communication with the international community through graphic design. Based on the above, this study marked (Aesthetics of the Design Idea and its Communication Role in the Graphic Outcome) comes to clarify the topic through three chapters, including the first chapter, which was devoted to the research methodology, the research problem and the need for it, which were identified by the following question (What are the aesthetics of the design idea and what is its communicative role in Graphic creator)? The aim of the study was (to identify the aesthetics of the design idea and its communicative role in the graphic achievement) and included the importance of research and the limits of research as well as defining terms. The most important findings of the research are: 1- The concepts of aesthetic are relative and differ from person to person and from one situation to another. 2- The aesthetic in graphic design is an objective phenomenon, not moody or subjective as in the plastic art, and this appeared in all studied samples. 3- The aesthetic value of the thing is related to its functional and utilitarian value, especially in design, the aesthetic stems from its functional and utilitarian value and then comes other material values ​​and this appeared in all samples 4- The selected samples have provided unlimited global communication messages by employing visual messages that carry deep meanings and implications for the international community in their different languages, needs and ideas, so it was a universal language. 5- The aesthetic value in designing logos stems from its moral, heritage and human value. 6- The design ideas in the design of logos were distinguished by their clarity and simplicity of the idea, as they moved away from the complexity in proposing the design idea and this appeared in the all samples.